PEDAGOGICAL ASPECTS OF FORMING VALUES IN MIGRANT STUDENTS - Eshonjonov Bobir Zafarjonovich (International Scientific and Current Research Conferences, 2025)
The article is devoted to the study of methods of harmonizing national and universal values in children from migrant families studying in general secondary schools. In the context of migration processes, it is important for the younger generation to preserve their own culture and values, while also adopting the values of the new society. The article analyzes the essence of national and universal values, their interdependence, and the tasks of general secondary schools in this regard.